A avaliaç\~ao de ciclo de vida como ferramenta para a formulaç\~ao de políticas públicas no Brasil - Osmar Coelho Filho; Nilo Luiz Saccaro; Gustavo Luedemann (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Life cycle analysis (LCA) has been used worldwide to guide innovation improving performance actions of and in production systems directed to the environmental sustainability. However, even with the wide dissemination of LCA internationally, the tool is still not very well known and applied in Brazil. This research is dedicated to examining the stages of construction of the LCA, its potential for application in different economy sectors and its use constraints in Brazilian public policies. The methodology Pressure-State-Response was used to assess the Pressure factors and future scenarios for LCA use in the country, including the information governance necessary for its implementation. A half-open questionnaire based on literature review on the topic was applied with representative stakeholders from academia, the public sector and the productive sector. The perception of stakeholders indicated that LCA as an international market trend, seen as the paradigm for the eco-design of products and processes, which boosts its increasingly popularization among private agents, although its cost is still prohibitive for medium and small enterprises. New national approaches to the implementation of the LCA (modular, staged) have been proposed to overcome this problem by allowing LCA to be seen not only as command and control environmental policy instrument but also as a tool for innovation management. The advancement of information technology and databases convergence was identified as relevant for accelerating the LCA approaches implementation adapted to different economic sectors. There is some consensus that LCA use in the public policies construction and evaluation require a preliminary stage of dissemination on Life Cycle Thinking (LCT) among the stakeholders. The main research conclusion is that LCA can play an important role in the pursuit of environmental sustainability in Brazil, in the context of climate and environmental challenges that will affect the production systems performance.
Keywords: Q01; 330; life cycle; public policy; environment